2020
DOI: 10.1093/jcr/ucaa005
|View full text |Cite
|
Sign up to set email alerts
|

The Smartphone as a Pacifying Technology

Abstract: In light of consumers’ growing dependence on their smartphones, this article investigates the nature of the relationship that consumers form with their smartphone and its underlying mechanisms. We propose that in addition to obvious functional benefits, consumers in fact derive emotional benefits from their smartphone—in particular, feelings of psychological comfort and, if needed, actual stress relief. In other words, in a sense, smartphones are not unlike adult pacifiers. This psychological comfort arises fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
134
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(138 citation statements)
references
References 44 publications
3
134
0
1
Order By: Relevance
“…In the space below please describe what made you upset, including your thoughts and feelings about the topic or event.After participants completed the disclosure task, they were asked to use the same device to respond to a set of scales that measured the proposed drivers of depth of disclosure: Psychological comfort. Participants responded to five items adapted from Melumad and Pham (2020) that measured the extent to which they associated feelings of psychological comfort with the use of their assigned device (1 = “Not true at all,” and 7 = “Very true”): (1) “Using my smartphone (PC) provides a source of comfort,” (2) “Having my smartphone (PC) with me makes me feel secure,” (3) “When I am using my smartphone (PC) I feel I am in my safe space,” (4) “Just holding my smartphone (PC), no matter what I do with it, makes me feel comforted,” and (5) “Touching or holding my smartphone (PC) makes me feel calmer.” Responses to these items were averaged into an index of “psychological comfort” (α = .88). Attentional narrowing on disclosure. Participants indicated the extent to which they agreed with each of three statements about how they felt while writing about their personal experience: (1) “I drowned out my environment when writing,” (2) “I got lost in what I was writing,” and (3) “I felt a sense of privacy when writing” (1 = “Not true at all,” and 5 = “Very true”).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the space below please describe what made you upset, including your thoughts and feelings about the topic or event.After participants completed the disclosure task, they were asked to use the same device to respond to a set of scales that measured the proposed drivers of depth of disclosure: Psychological comfort. Participants responded to five items adapted from Melumad and Pham (2020) that measured the extent to which they associated feelings of psychological comfort with the use of their assigned device (1 = “Not true at all,” and 7 = “Very true”): (1) “Using my smartphone (PC) provides a source of comfort,” (2) “Having my smartphone (PC) with me makes me feel secure,” (3) “When I am using my smartphone (PC) I feel I am in my safe space,” (4) “Just holding my smartphone (PC), no matter what I do with it, makes me feel comforted,” and (5) “Touching or holding my smartphone (PC) makes me feel calmer.” Responses to these items were averaged into an index of “psychological comfort” (α = .88). Attentional narrowing on disclosure. Participants indicated the extent to which they agreed with each of three statements about how they felt while writing about their personal experience: (1) “I drowned out my environment when writing,” (2) “I got lost in what I was writing,” and (3) “I felt a sense of privacy when writing” (1 = “Not true at all,” and 5 = “Very true”).…”
Section: Methodsmentioning
confidence: 99%
“…The first factor that we argue enhances depth of disclosure on one’s smartphone versus PC is the increased psychological comfort that consumers tend to derive from their phone (e.g., Clayton, Leshner, and Almond 2015; Vahedi and Saiphoo 2018). For example, Melumad and Pham (2020) found that after an induction of stress, participants assigned to engage in a task on their smartphone reported a greater increase in psychological comfort (and thus, greater relief from stress) than those assigned to engage in the same task on their laptop, or even an otherwise similar smartphone belonging to someone else.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Some consumers are likely to prefer logos and products that are themselves bounded to compensate for the feelings of loss of control ( Cutright 2012 ). In addition, Melumad and Pham (2020) show that consumers turn to their smartphone when feeling stressed and the personal nature, portability, and haptic gratification offer stress relief and psychological comfort. Marcoux (2017) uncovers how New Yorkers used souvenirs both to remember and forget the 9/11 terrorist attacks on the Twin Towers in New York in 2001.…”
Section: Consumer and Market “Adaptive” Responsesmentioning
confidence: 99%